Guidelines for the surface preparation/rehabilitation of existing concrete and asphaltic pavements prior to an asphaltic concrete overlay - Titi, Hani; Wen, Haifang (Wisconsin Highway Research Program, 2005)
A large percentage of the asphaltic paving projects performed in Wisconsin are asphaltic overlays of existing concrete or asphaltic pavements. Due to varying performance of overlay, a standard set of guidelines is needed to determine the amount of surface preparation which provides a consistency along with more accurate and stable project budgets for this type of work. Literature review of Wisconsin Department of Transportation (WisDOT) and national practices of pre-overlay repair of existing concrete and asphaltic pavements was conducted. Previous asphalt overlay projects were reviewed and overlay performance was analyzed. In addition, three overlay projects during 2004 construction season were studied in the field. For asphalt overlay of existing concrete pavements, it was found that overlays with doweled concrete base patching performed best, followed by non-doweled concrete base patching and then asphaltic base patching. Partial depth repair is needed to fix the medium severity transverse cracks and longitudinal/transverse distressed joints in existing concrete pavement. A minimum of 3 in., practically 3 1/2 in., overlay thickness was found to be able to mitigate reflective cracking in overlay. All high-severity joints/cracks/patches should be repaired. The current International Roughness Index (IRI) in overlay was highly correlated with initial IRI of overlay, indicating the importance of profile index. The roughness prediction model used in the NCHRP 1-37A 2002 design guide was calibrated with locally available data. For asphalt overlay of existing asphalt pavements, block cracking in existing asphalt pavement does not adversely affect the overlay when milling is used. Existing asphalt pavement with extensive alligator cracking should be pulverized to prevent the reflection of underlying alligator cracking. Milling the existing asphalt pavement can not eliminate the reflection of transverse cracking in existing asphalt pavement. The ratio of overlay thickness to milling depth should be kept a minimum of 3 to prevent longitudinal cracking from re-occurring in overlay. A set of guidelines was developed to be included in the Facility Development Manual and Construction and Material Manual.
110 p.
Keywords: Transverse cracking; Thickness; Surface preparation; Rehabilitation (Maintenance); Reflection cracking; Patching; Milling; Overlays (Pavements); Literature reviews; Guidelines; Field studies; Concrete pavements; Comminution; Bituminous overlays; Alligator cracking; Asphalt pavements